Maternal Age Distribution of Down-Syndrome at Pediatric Growth and Development Clinic, 2015-2019 - Musdalipa, Musdalipa; Wulandari, Rini; Maddeppungeng, Martira (Fakultas Kedokteran Universitas Muslim Indonesia, 2021)
Introduction: Down Syndrome is a common chromosome abnormality among infants. This condition is Present in 1 over 800 deliveries. Advanced maternal age is a risk factor for Down syndrome. Other miscellaneous factors are radiation, infection, autoimmune and paternal age. The Aim is to determine maternal age distribution of Down syndrome at pediatric growth and development polyclinic, Wahidin Sudirohusodo hospital. Methods: A Descriptive study. Study population was all outpatients at Pediatric Growth and Development polyclinic, Wahidin Sudirohusodo hospital in Makassar 2015-2019. Samples in this study were collected from total sampling of population data that met the criteria of new Down syndrome patients with complete medical records Results: This study found 237 new pediatric down syndrome patients admitted to growth and development polyclinic from January 2015 – December 2019, 95 complete medical records from 237. 52% (49) boys, 48 % (46) girls from 95 children. No gender difference was found in the presentation. Parental age of Down syndrome patients, the most advanced maternal age was >35, found 46 (48,42%), the most advanced paternal age was >35, found 63 (66,32%). Parity < 3rd, the most maternal age between 25-35 (23,16%), parity > 3rd, the most maternal age was >34, found 30 (31,57%). Conclusion. Advance maternal and/ or paternal age is a risk factor of Down Syndrome.